(untitled) (diségno, 2025)
The design process is inherently representational; drawing and similar tools reduce cognitive load and enable the generation, recording and reuse of ideas. This process supports the internal dialogue that fosters innovative solutions. Representations have both external forms, such as drawing and modelling, and internal forms, such as imagination and thought, while language is a crucial tool that guides the processes of thinking and doing. While verbal expressions convey abstract thoughts and provide insight into the problem, visual representations concretise abstract ideas. This study analyses the transitions between verbal and visual representational languages, examining how ideas are transformed into representations, what comes to the fore, and what is left behind in this process. The ways designers structure ideas, the gaps that occur in the transitions between representational languages, and the ways they cope with these gaps are revealed through an examination conducted through drawing and physical modelling. The study positions drawing as a bridge between languages, moving it beyond being a mere representational tool in the design process, and focuses on the role of drawing in framing, organising and translating design ideas, making it an indispensable component of the discovery process.